PELATIHAN TEKNIK BERUNDING PERJANJIAN KERJA BERSAMA (PKB) PADA SERIKAT PEKERJA DIBAWAH NAUNGAN SARBUMUSI - Utami, Yeski Putri; Lagandhy, Langga; Saputra, Eka; Djohan, Henry Anggoro (LPPM ITB AAS Indonesia Surakarta, 2024)
The aim of this training activity is to increase the knowledge and skills of Labor Union (LU) chairmen and members in Collective Work Agreement (CWA) negotiations. It is hoped that LU under the patronage of Sarbumusi can use more effective negotiation techniques in order to reach an agreement that benefits both parties, LU and its enterprise. This training was arranged to strengthen SP's position in negotiating with management and promote healthy and productive working relationships. The materials consist of the introduction to Collective Work agreement (CWA), its regulation, and negotiation techniques. The methods used were divided into two stages; preparation and implementation – presentation, discussion, case-study and simulation. The impact of this training was excellent because LU was provided with basic knowledge as well as the key to use negotiation techniques in pursuing the better prosperity for all workers, especially the members of LU. Keywords: Collective Work Agreement (CWA), Labor Union (LU), Negotiation techniques